Effects of daily static stretch training over 6 weeks on maximal strength, muscle thickness, contraction properties, and flexibility - Wohlann, Tim; Warneke, Konstantin; Hillebrecht, Martin; Petersmann, Astrid; Ferrauti, Alexander; Schiemann, Stephan (Frontiers in Sports and Active Living, 2023)
Purpose Static stretch training (SST) with long stretching durations seems to be sufficient to increase flexibility, maximum strength (MSt) and muscle thickness (MTh). However, changes in contraction properties and effects on muscle damage remain unclear. Consequently, the objective of the study was to investigate the effects of a 6-week self-performed SST on MSt, MTh, contractile properties, flexibility, and acute response of creatine kinase (CK) 3 days after SST. Methods Forty-four participants were divided into a control (CG, n = 22) and an intervention group (IG, n = 22), who performed a daily SST for 5 min for the lower limb muscle group. While isometric MSt was measured in leg press, MTh was examined via sonography and flexibility by functional tests. Muscle stiffness and contraction time were measured by tensiomyography on the rectus femoris. Additionally, capillary blood samples were taken in the pretest and in the first 3 days after starting SST to measure CK. Results A significant increase was found for MSt (p < 0.001, η2 = 0.195) and flexibility in all functional tests (p < 0.001, η2 > 0.310). Scheffé post hoc test did not show significant differences between the rectus femoris muscle inter- and intragroup comparisons for MTh nor for muscle stiffness and contraction time (p > 0.05, η2 < 0.100). Moreover, CK was not significantly different between IG and CG with p > 0.05, η2 = 0.032. Discussion In conclusion, the increase in MSt cannot be exclusively explained by muscular hypertrophy or the increased CK-related repair mechanism after acute stretching. Rather, neuronal adaptations have to be considered. Furthermore, daily 5-min SST over 6 weeks does not seem sufficient to change muscle stiffness or contraction time. Increases in flexibility tests could be attributed to a stretch-induced change in the muscle–tendon complex.